Component-resolved diagnostics in pediatric wheat-dependent exercise-induced anaphylaxis: A case report: A case report - Miyamoto, Manabu; Maruyama, Nobuyuki; Yoshihara, Shigemi (Allergologia et Immunopathologia, 2025)
Wheat-dependent exercise-induced anaphylaxis (WDEIA) is a subtype of immunoglobulin E (IgE)-mediated wheat allergy characterized by symptoms from wheat intake followed by physical exercise. Although omega-5 gliadin-specific IgE (sIgE) is widely used for diagnosing WDEIA, its sensitivity is lower in children than in adults. This report describes a 13-year-old male with suspected wheat allergy who experienced anaphylaxis following wheat ingestion and exercise. ImmunoCAP results revealed positive sIgE for wheat and gluten but negative results for omega-5 gliadin. An open-label oral food challenge combined with exercise confirmed the diagnosis of WDEIA. Notably, alpha/beta gliadin sIgE was detected using an enzyme-linked immunosorbent assay with the patient’s serum, suggesting that alpha/beta gliadin can serve as an alternative marker in pediatric cases where omega-5 gliadin sIgE is undetectable. This suggests that omega-5 gliadin sIgE alone may not be appropriate for diagnosing WDEIA in children. Instead, utilizing a combination of other wheat protein components may enhance both sensitivity and specificity in diagnosis.